Covid 19 and the Turkish labor market: Heterogeneous effects across demographic groups - Altan Aldan; Muhammet Enes Çıraklı; Huzeyfe Torun (Central Bank Review (CBR), 2021)
The aim of this paper is to detect the effects of the Covid-19 pandemic on several labor market indicators and to identify the heterogeneity of these effects across different demographic groups in the Turkish labor market. To this aim, we use the quarterly Turkish household labor force surveys which cover the period between 2005 and 2020. We find that pandemic decreased employment and labor force participation of almost all groups. The effect on women was more prominent in comparison with men. We also find heterogeneity with respect to age. Finally, our results show that the least educated were more negatively affected by the pandemic.
Keywords: J16; J21; J23; 330; Covid-19; Employment; Labor force participation; Unemployment